Między prasą a cyberprzestrzenią. Analiza porównawcza gazety i serwisu www na przykładzie „Dziennika Łódzkiego” - Bogdańska, Jolanta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article presents the results of a comparative analysis of the regional newspaper “Dziennik Łódzki” (the oldest in the Łódź region) and its website www.dzienniklodzki.pl. The analysis concerned the scope of content exchange between the printed edition and the website, similarities and differences in journalistic publications both in traditional form and online, as well as a comparison of the hierarchy of importance of publications and a comparison of press genres – online and in the newspaper.